A assessment of abundance, habitat preference, diversity and people's perception on use of wild dioscorea species in Gongdu Gewog, Mongar - Lungten Wangdi (CNR, Lobesa Lungten Wangdi, 2022)
includes acknowledgement and abstract
Keywords: Thesis